Adherence to Consensus Guidelines for the Management of Labor Arrest Disorders in a Single Academic Tertiary Care Medical Center - Alrais, Mesk A.; Ankumah, Nana-Ama E.; Amro, Farah H.; Barrett, Tyisha; Folh, Kendra; Chen, Han-Yang; Sibai, Baha M.; Blackwell, Sean C. (American Journal of Perinatology, 2019)
Objective To evaluate the degree of adherence to the new the American College of Obstetricians and Gynecologists/Society for Maternal–Fetal Medicine guidelines in labor arrest management.Study Design A retrospective study of term, live, singleton deliveries with intrapartum primary cesarean delivery solely for failed induction of labor or labor arrest. Adherence was defined according to the Safe Prevention of the Primary Cesarean Delivery 2014 criteria. We evaluated adherence and compared maternal and perinatal outcomes, delivery time frame, and billing provider. Multivariable Poisson regression models with robust error variance were used to calculate adjusted relative risk (aRR) and 95% confidence interval (CI).Results Two-hundred six deliveries met the inclusion criteria; 73% were deemed not adherent to the guidelines. The majority of cases were under the care of nonacademic private practice OB/GYN physicians. The adherence rate was higher in the active phase of labor (45%) than in second stage (17%) and latent phase (14%). There were no differences in perinatal outcomes between the two groups. The adherence to guidelines was higher among academic OB/GYN physicians (aRR, 2.24, 95% CI, 1.49–3.36) and during the weekday–night shift (aRR, 1.81, 95% CI, 1.10–2.98).Conclusion Despite recent guidelines aimed to reduce the primary cesarean delivery rate, most cesarean deliveries performed for labor arrest disorders were not adherent to the guidelines.
Keywords: adherence; cesarean delivery; consensus guidelines; failed induction; labor arrest